Sharia Compliance Supervision Management at KSPPS Bmt Alhikmah Semesta - Arida Risqiana; Miswan ansori (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
The importance of Sharia Compliance in the Sharia financial industry, with a focus on BMT Al Hikmah Semesta. Sharia Compliance supervision management at BMT is considered crucial to ensure compliance with sharia principles, where the Sharia Supervisory Board (DPS) plays an important role in overseeing this compliance. The strategy implemented by BMT Al Hikmah Semesta includes implementing a digital attendance system and establishing a Sharia Compliance Division. Although this article provides a valuable contribution to the understanding of Sharia compliance monitoring activities in the field of Sharia finance, there are several limitations in the research that need to be taken into account, such as weaknesses in the corporate governance of Islamic financial institutions that may affect the performance of these institutions. In this context, the Sharia Supervisory Board (DPS) at BMT Al Hikmah Semesta has an important role in enforcing sharia compliance, by providing fatwas, and recommendations regarding new products and services, as well as carrying out routine monitoring of operational activities. Management needs to increase support for DPS performance and provide education to employees to strengthen the culture of sharia compliance at BMT, so that it can increase effectiveness, maintain quality and increase members' trust in the sharia financial industry.